Characterization of the journalistic exercise in Chilean presidential debates: a comparison between women and men in their role as interviewers - Ortega-Gunckel, Constanza (2021)
The following research presents the results of a mixed exploratory study, whose objective is to identify if the characteristics of the journalistic exercise are influenced by the gender approach, in the context of the presidential debates carried out in Chile. As a corpus of analysis, the transcripts of seven televised presidential debates, organized by ANATEL (National Television Association) and broadcast between 1989 and 2017, were used. Based on a content analysis of 758 statements (broadcast by 13 female and 22 male journalists) and constant comparison analysis, it was possible to identify the following: contrary to what the theory describes, female journalists behave similarly to their male peers, constructing their questions mainly on challenging news topics, focusing them on the execution and financing of public policies, and supporting them with the use of data. Also, they adopt a civic-guard dog role, responding to traditional expectations regarding the exercise of journalism; in contrast, men assume a civic-antagonistic role. In conclusion, the debates, being a neutral instance with pre-established rules, diminish the inequity and inequalities among journalists according to their gender, reducing the existing barriers in the newsrooms.